Season-long changes in COD performance, jump, and flexibility in elite youth soccer players - Palco, M.; Giuca, C.; Giorgio, A.; Leonetti, D.; Simonetta, R.; Familiari, F. (Frontiers in Sports and Active Living, 2026)
Background: In elite youth soccer, the interplay between the development of key physical qualities, change-of-direction (COD) performance, explosive strength, and flexibility, remains poorly understood. Conventional training often assumes transfer effects, yet empirical evidence on how these qualities co-occur within elite youth cohorts across a competitive season remains limited. We tested the hypothesis that flexibility and explosive strength would be positively associated with COD performance at end-season (T2).